2020
DOI: 10.1111/hae.14120
|View full text |Cite
|
Sign up to set email alerts
|

Illness cognitions associated with health‐related quality of life in young adult men with haemophilia

Abstract: Introduction and Aim: Knowledge on patterns of beliefs about the illness (illness cognitions) can provide insight into individual differences in adjustment to haemophilia. The current study aimed to identify (a) which sociodemographic and disease characteristics were associated with illness cognitions and (b) which illness cognitions were associated with health-related quality of life (HRQOL) in young adult men with haemophilia, besides sociodemographic and disease characteristics. Methods: Young adult men (18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…28 Consistent with this assumption, other authors explained this association with the assumption that the HRQoL would be influenced by the level of acceptance of the infection and the ability to adapt to illness. 38,41,42,43 Our study underlines another aspect referred to as the HRQoL. It has been observed that comorbidities affect the global perception of health but not mental health.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…28 Consistent with this assumption, other authors explained this association with the assumption that the HRQoL would be influenced by the level of acceptance of the infection and the ability to adapt to illness. 38,41,42,43 Our study underlines another aspect referred to as the HRQoL. It has been observed that comorbidities affect the global perception of health but not mental health.…”
Section: Resultsmentioning
confidence: 77%
“…Jones and colleagues focus on HIV infection and argue that there is a possible risk factor for the appearance of psychological symptoms, even before noticeable physical signs. [36][37][38][39][40] The psychological dynamics in HIV-positive PWH were analyzed over the years by considering only parameters such as stress and the relationship between infections. Specifically considering HIV and mental suffering, the association is still confused even now that vaccinations and antiretroviral therapies slow the progression of the disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quant aux avantages perçus, ils ont eu des liens moyens avec le bienêtre psychologique. Limperg et al (2020) ont découvert au cours de leur étude qu'une plus grande acceptation de l'hémophilie chez les jeunes adultes hommes était associée à une meilleure qualité de la vie liée à la santé. A l'opposé, une plus grande impuissance était corrélée à une pire qualité de vie liée à la santé.…”
Section: Introductionunclassified